Choice experiment (CE) in estimating the value of living heritage conservation in Melaka city - Chiam, Chooi Chea; Radam, Alias; Abdul Rahim, Khalid; Yacob, Mohd Rusli (Melaka Museums Corporation and Faculty of Law, Universiti Kebangsaan Malaysia, 2013)
There are two common methods for measuring 'Willingness to Pay' (WTP) in estimating the value of living heritage, namely the reveal preference (RP) and the stated preference (SP) method. However this paper aims to use another method called choice experiment (CE) method in said measurement. The data in this paper was collected in Melaka city as Melaka city has been listed as UNESCO World Heritage Site on 7 July 2008. This paper studies the visitors' WTP in conserving the living heritage in Melaka city using choice experiment method. Hopefully the results of this study can bring an insight to the policy-makers on the value of conserving the living heritage in Melaka city by its visitors.